2017
DOI: 10.1111/ajgw.12327
|View full text |Cite
|
Sign up to set email alerts
|

Zygotorulaspora florentinaandStarmerella bacillarisin multistarter fermentation withSaccharomyces cerevisiaeto reduce volatile acidity of high sugar musts

Abstract: Background and Aims: The possibility to decrease wine volatile acidity (VA) is an important aspect in wine production. This applies in particular to wines that are produced from musts with high sugar concentration, where the osmotic pressure promotes an increase in acetic acid production by Saccharomyces cerevisiae. This study aimed to identify suitable yeast strains and fermentation temperature to undertake the alcoholic fermentation of high sugar musts. Methods and Results: To lower VA during fermentation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Instead, the increase in volatile acidity observed in the fermentation inoculated with S. bacillaris/S. cerevisiae is in agreement with the results obtained by Whitener et al [55] but in contrast with previously published works showing C. zemplinina (synonym S. bacillaris) able to reduce the amount of acetic acid when in mixed culture with S. cerevisiae [5,[10][11][12]. Nisiotou et al [56] found lower acetic acid concentration in sequential fermentation S. bacillaris/S.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Instead, the increase in volatile acidity observed in the fermentation inoculated with S. bacillaris/S. cerevisiae is in agreement with the results obtained by Whitener et al [55] but in contrast with previously published works showing C. zemplinina (synonym S. bacillaris) able to reduce the amount of acetic acid when in mixed culture with S. cerevisiae [5,[10][11][12]. Nisiotou et al [56] found lower acetic acid concentration in sequential fermentation S. bacillaris/S.…”
Section: Resultssupporting
confidence: 90%
“…cerevisiae mixed starters [8,9]. Starmerella bacillaris (synonym Candida zemplinina) contributes to reduce the amount of acetic acid in mixed fermentation with S. cerevisiae [5,[10][11][12]. Moreover, this yeast is usually characterized by high glycerol production [11,[13][14][15][16][17] and low ethanol yield [16,[18][19][20] making it an interesting tool to increase the wine sweetness and modulate the ethanol content.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the same authors [47], studied the possibility to decrease wine volatile acidity in mixed fermentations with Zygotorulaspora florentina and Starmerella bacillaris (syn., Candida zemplinina). Independent of fermentation temperature, the mixed fermentations with Z. florentina performed best to reduce volatile acidity, thus being a valuable tool for performing fermentation of high-sugar musts.…”
Section: Zygosaccharomyces Florentinus/zygotorulaspora Florentina: Vomentioning
confidence: 99%
“…The type strain of the yeast Zygotorulaspora florentina (VTT C-94199; CBS 746) has been isolated from must. Other strains have been isolated from grapes [10], plant material and soft drinks [11]. The former name of the species was Zygosaccharomyces florentinus, but based on DNA analysis it was reclassified as a Zygotorulaspora species, joining Zygotorulaspora mrakii, in the genus [12].…”
Section: Introductionmentioning
confidence: 99%
“…In cofermentation with a commercial ale yeast, the species was found to affect positively beer flavor [13]. The species has also been studied for winemaking [10,15,16], and in those studies, the species has been found to promote the levels of higher alcohols and esters, and to reduce volatile acidity in cofermentations with a commercial wine strain of S. cerevisiae. The positive effects on aroma, maltose-fermentation capability and the reported inability to grow at 37 • C (culture collection data, [11]) make the species an interesting candidate for brewing trials.…”
Section: Introductionmentioning
confidence: 99%